Effect of harvesting stage and storage condition on post-harvest quality and sensory acceptability of mango fruit in Gamo Zone, Southern Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2023)
The effect of harvesting stages (mature green, half-ripe and full ripe) and storage conditions (zero energy cool chamber, wooden box and underground storage) on post-harvest quality and sensory acceptability of mango fruit was evaluated. Three harvesting stages of mango fruit were harvested and 10 kg of mango fruit was stored in three storage conditions until the end of the storage period. Spoilage and weight loss of mango fruit were recorded from storage in three-day intervals. All samples were analyzed for Post-harvest quality of mango fruit before and after storage at Arba Minch University, Abaya Campus Chemistry laboratory, and sensory acceptability was evaluated by using untrained 45 panelists at the end of the storage period. Completely Randomized Design in factorial arrangement with three replications was used to evaluate the shelf life and postharvest quality of mango fruit.  Weight loss, spoilage, firmness and total soluble solids of mango fruit were increased while vitamin C, moisture content and titratable acidity were decreased with increased storage time. The vitamin C content of mango fruit was highest at half ripe in a zero energy cool chamber and was lowest at full ripe harvested in a wooden box after the end of the storage period. The highest overall acceptability of mango fruit was observed at the half-ripe harvested stage in zero energy cool chambers while the lowest was observed at the mature green harvested stage mango fruit in a wooden box after the end of the storage period. Based on the current study, half ripen mango fruit in zero energy cool chamber storage recorded the least percent of weight loss, spoilage amount, maximum shelf life and quality, especially vitamin C content and higher overall acceptability. Further study will be needed on the microbial quality of mango fruit in different harvesting stages and storage conditions during storage periods.Int. J. Agril. Res. Innov. Tech. 12(2): 82-87, December 2022